PEMBERDAYAAN MASYARAKAT DALAM PEMETAAN DAN OPTIMALIASI POTENSI DESA WISATA SEGAJIH LIVE IN EDUCATION KULON PROGO - Yoga Yoga Sahria; Septiono Eko Bawono (Jurnal Pengabdian Masyarakat Multidisiplin, 2023)
Desa Wisata (Desa Wisata) Segajih is located in Hargotirto, Kulon Progo, Yogyakarta, Indonesia. The village is known for its stunning natural beauty, such as green hills, waterfalls, rivers, and vast rice fields. In addition, in Segajih Tourism Village there are also several homestays / inns and serve regional specialties. Segajih Tourism Village carries the concept of "Live in Education," where tourists can experience an educational experience that includes the process of batik making, ant sugar making, painting, playing gamelan, and other activities. However, there is a problem in Desa Wisata Segajih Tourism Village, which is not optimal in identifying tourism potential and mapping that provides information to visitors about the relative location of tourism potential. Community service methods carried out include observation, counseling, FGD (Focus Group Discussion), discussion, training, and mentoring. The purpose of this community service is to empower the community in mapping and optimizing the potential of Desa Wisata Segajih to be more advanced and prosperous for the village community. The results of this PKM are producing a map of the potential of Segajih tourism village and its surroundings, besides that this PKM also produces the identification of potentials, problems and solutions.